Increased event-related potential latency and amplitude variability in schizophrenia detected through wavelet-based single trial analysis - Roth, Alexander; Roesch-Ely, Daniela; Bender, Stephan; Weisbrod, Matthias; Kaiser, Stefan (International journal of psychophysiology, 2007)
Analysis of single-trial event-related potentials can potentially yield important information about the underlying brain dynamics. We were specifically interested in latency and amplitude variability of the P3 component in patients with schizophrenia. For this purpose we developed a method for analyzing single-trial ERPs based on a wavelet smoothing algorithm, which is presented in detail. This method was applied to data from schizophrenic patients and healthy controls in an auditory Go/Nogo task. We found a significant increase of latency variability in the schizophrenic group at electrode Fz (frontal midline) and increased amplitude variability at electrode Pz (parietal midline). These results support the concept of increased cortical noise in patients with schizophrenia.
Gesehen am 14.12.2021